Thermodynamic Stability of Polysulfone/Zinc Salt Membrane - Nor Azmi Tarmizee, Aliff Ikram; Yunos, Muhamad Zaini (Research Progress in Mechanical and Manufacturing Engineering, 2024)
In some applications, membrane thermodynamic stability may pose an important issue. Thermal instability may lead to membrane degradation, performance loss, or changes in membrane characteristics over time. This study focused on determining the thermodynamic stability of polysulfone (PSf) membrane and characterizing the membrane based on morphology. The membrane was created through a phase inversion method, using PSf as the base polymer, N-methyl-2-pyrrolidone (NMP) as the solvent, and zinc nitrate, zinc chloride, and zinc acetate as nonsolvent additives in varying concentrations. To determine the precipitation curve on a ternary phase diagram, cloud point measurements were conducted. The relationship between PSf concentration and the time required for the membrane to undergo phase separation was established. The results revealed a gradual increase in the precipitation rate as the PSf concentration rose. The findings indicate that higher PSf concentrations lead to greater stability of the dope solution. A recommendation to achieve better results on the thermodynamic stability aspect would be to increase the polymer to zinc salt ratio.